Нюша, Павлуша и Я: рассказы / Нина Ермолаева - Ермолаева Нина Георгиевна (Для семейного чтения, 2016)
Экземпляры: ф.4 (20170626) / Инвентарный номер: 2768 / Цена: / Сис.шифр: 84(2Рос.Удм)6-4 / Авт.знак: Е 74 / ГРНТИ: 17.82.93 / ББК: 84(2Рос.Удм)6-44